DEVELOPMENT OF A LIBRARY ARRAGEMENT MODEL FOR STIMULATION OF EARLY LITERACY OF CHILDREN IN AL-IRSYAD AL-ISLAMIYYAH KINDERGARTEN in KABUPATEN JEMBERT - Hirmawan, Rafiiqaa Ramadhan; Saputri, Senny Weyara Dinda; Zahro, Indah Rohmatuz (Jurnal PAUD: Kajian Teori dan Praktik Pendidikan Anak Usia Dini, 2024)
The arrangement of the children's library space has an important role, which can make children feel comfortable and at home when they are inside. Literacy activities at Al-Irsyad Al-Islamiyyah Jember Kindergarten are only carried out through exercise books or spelling guidelines provided by the school. The library at Al-Irsyad Al-Islamiyyah Jember Kindergarten in the previous arrangement was only a reading corner so it needed to be developed into a library so that it could be visited by the whole group. The aim is to describe the process of developing a library arrangement model for children's early literacy stimulation and find out the results of developing a library arrangement model for children's early literacy stimulation. The analysis stage is to find the necessary needs such as lighting and wall decoration to design. The design stage is to design the arrangement of the area. The development stage is to test the validation of the design that has been applied in reality. The implementation stage is to directly practice the results of the library arrangement for literacy stimulation. The method used was observation, interview, and documentation. The results of the research used the results of the expert validity test the average score of the overall validation was 88 with a very feasible category. The practicality test received an average score of 73 with practical criteria. The effectiveness test gets an overall average score seen by children doing literacy activities in the library getting a score of 75 with effective criteria.